Accommodating discontent: youth, conflict and the housing question in Hong Kong. Issue 1 (2nd January 2018) - Forrest, Ray; Xian, Shi
Abstract: Young people across many societies face growing problems in making the transition from the parental home to independent living. Rising house prices and the lack of affordable alternatives to home ownership is most commonly blamed. This paper explores these issues in relation to young people in Hong Kong. The paper argues that the housing question in Hong Kong has distinct local characteristics and cannot be disconnected from wider political and economic tensions. It also shows that the housing choices and views of young people are shaped by more than issues of cost and access. The paper draws on a unique data-set which explores the attitudes and expectations with regard to housing among young people in Hong Kong. Addressing the housing problem is widely regarded as a political priority and essential to maintain social cohesion. However, political imperatives and economic interests are pulling in different directions.